Инновационный сектор экономики региона в период экономического кризиса; Инновации; № 11 - Губин Е. П. Евгений Петрович; Гуменников И. В. Илья Владимирович; Монастырная Е. Е. Елена Евгеньевна; Монастырный Е. А. Евгений Александрович (2014, 2014)
Заглавие с экрана